ELECTRONIC WASTE AWARENESS AND MANAGEMENT IN THE MUNICIPALITY OF TUBURAN, CEBU - Bajao, Naomi A.; Pepino, M; Celeste, N; Sarucam, J; Brigoli, Helen C.; Pontillas, Pedrito C. (Journal of Agriculture and Technology Management, 2018)
The world is now facing the great effect of the rapid growth of information technology. The electronic waste or E-waste has been the major contributor of solid waste throughout the globe that had caused the contamination of the global environment. Thus, this study assessed the electronic waste in the Municipality of Tuburan Cebu. Questionnaires were distributed to the 13 barangays in the municipality of Tuburan with simple questions answerable by “Yes” or “No”. There were 1,115 respondents (families) over 13 barangays in Tuburan, Cebu. Results showed that more than half of the respondents still need complete awareness about electronic waste, its composition, proper handling, and its effects to the environment. An alarming value shows that 721 or 64.66 percent of the 1,115 respondents said that there are no waste collectors in their area. This simply means that more than 50 percent of the total number of respondents would end up throwing and dumping their waste including E-waste; anywhere or in the open landfill. It shows that respondents need complete awareness about E-waste; particularly, the nature of electronic waste, proper handling, and the negative effects to the environment and their effects to the human health and other living animals. The absence of waste collectors in most barangays has created big impact to the surroundings already. Moreover, some respondents have thought that these E-wastes just mean nothing to the waste collectors. Waste collectors must be strictly assigned by the LGU to some specific areas to closely monitor and confine the waste disposal of each household. It will also be good if a separate collector for E-waste can be provided in each locality.